Functional roles of circular RNAs during epithelial-to-mesenchymal transition - Shang, Bing-Qing (Mol Cancer, 2019)
Cancer has become a major health issue worldwide, contributing to a high mortality rate. Tumor metastasis is attributed to the death of most patients. Epithelial-to-mesenchymal transition (EMT) plays a vital role in inducing metastasis. During EMT, epithelial cells lose their characteristics, such as cell-to-cell adhesion and cell polarity, and cells gain motility, migratory potential, and invasive properties to become mesenchymal stem cells. Circular RNAs (circRNAs) are closely associated with tumor metastasis and patient prognosis, as revealed by increasing lines of evidence. CircRNA is a type of single-stranded RNA that forms a covalently closed continuous loop. CircRNAs are insensitive to ribonucleases and are widespread in body fluids. This work is the first review on EMT-related circRNAs. In this review, we briefly discuss the characteristics and functions of circRNAs. The correlation of circRNAs with EMT has been reported, and we discuss the ways circRNAs can regulate EMT progression through EMT transcription factors, EMT-related signaling pathways, and other mechanisms. This work summarizes current studies on EMT-related circRNAs in various cancers and provides a theoretical basis for the use of EMT-related circRNAs in targeted management and therapy.